PENGARUH PROFITABILITAS, HUTANG, DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2010-2015 - Nurfita, Lutfi (El-Hayah, 2017)
Abstract : The mining companies are closely related to waste and environmental pollution due to the exploitation of natural resources. The mining companies have high levels of industrial and environmental risks. The ex-mining environment can not be returned 100% as it was during the initial environmental conditions prior to mining activities. Therefore, the companies need to pay attention to the importance of carrying out social responsibility. This study aims to determine the effect of profitability, debt, and environmental performance on the corporate social responsibility disclosure in the mining companies listed in the Jakarta Islamic Index 2010-2015.The research method used is quantitative research method. The population in this study are all The Mining Companies listed in Jakarta Islamic Index 2010-2015 of 5 companies. This study uses purposive sampling with a sample of 5 Mining Companies Listed in the Jakarta Islamic Index 2010-2015. The dependent variable of this study is the corporate social responsibility disclosure. For independent variables include: the profitability, debt, and environmental performance. For data analysis method using the multiple linear regression, classical assumption test, model accuracy test, and t test.The results showed that partially the profitability and debt have no effect on the corporate social responsibility disclosure (0.229 and 0.625). While the environmental performance has an effect on the corporate social responsibility disclosure (0.000). Based on F test results, profitability, debt, and environmental performance have an effect on collectively on the corporate social responsibility disclosure in The Mining Companies Listed in The Jakarta Islamic Index 2010-2015 (F arithmetic 9,961). Suggestion from this research is The Mining Companies Listed in the Jakarta Islamic Index 2010-2015 should pay more attention to environmental performance because this variable influence to corporate social responsibility disclosureKeywords: Profitability, Debt, Environmental Performance, and Corporate Social Responsibility Disclosure.